Investigation of the Aerodynamics in Packed Metallurgical Furnaces with Tuyere Wind Entry - Yaroshenko YG; Shvydkii VS; Gordon YM; Scherbatskii VB; Shklyar FR; Bokovikov BA (The Australasian Institute of Mining and Metallurgy, 1975)
The paper presents, for the first time, a complete mathematical model of the flow of gases in packed beds which describes the processes of gas-mechanics in iron blast furnaces and other shaft type smelting units. Good correlation between calculated and experimental results was obtained confirming the adequacy of the model. It is shown that the uniformity of gas distribution is related to the tuyere size and the extent of its protrusion into the furnace and that these variables may be used to regulate gas distribution across the furnace diameter. It is also concluded that furnace height has no significant influence on gas distribution. The necessity for a mathematical description of raceway phenomena has been experimentally proved. Conclusions from theory are shown to have profound implication to furnace design and operation.